Ovarian endometriosis associated infertility: a modern view to the problem - Mekan R. Orazov; Marina B. Khamoshina; Marianna Z. Abitova; Lyudmila M. Mikhaleva; Snezhana V. Volkova; Dmitry G. Aryutin; Victoria B. Shustova (IP Berlin A.V., 2020)
This review summarizes current understanding of the pathogenesis of one of the most common forms of external genital endometriosis ovarian endometriomas. Due to their frequent occurrence in young women of reproductive age and extremely negative impact on the morphophysiological state of the ovaries, this disease makes a significant contribution to the structure of endometriosis-associated infertility. The main determinant of the negative effect of ovarian endometriomas on reproductive function is a decrease in ovarian reserve, which can occur either due to the direct gonadotoxic effect of the endometriod cyst itself, or due to the unintentional removal of healthy ovarian tissue during surgery or the use of aggressive methods of electrosurgery. Hence, the question of methods for achieving hemostasis during surgery in terms of iatrogenic effects on healthy ovarian tissue is debatable. The management strategy for patients with infertility associated with ovarian endometriosis consists of two components: surgical treatment and/or the use of assisted reproductive technologies. Laparoscopic cystectomy is indicated for cysts larger than 3 cm. Repeated surgical interventions in case of endometriosis do not improve fertility outcomes. Assisted reproductive technologies methods should be considered as a priority tactic in patients of older reproductive age with low ovarian reserve indicators or infertility duration of more than 2 years, as well as in cases of recurrent ovarian endometriomas. Management of such patients must be personalized and take into account the age, state of the ovarian reserve, duration of infertility, stage and number of surgical interventions for this disease.